Polietes Rondani 1866 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Polietes Rondani, 1866 Polietes Rondani, 1866: 91. Type-species: Musca lardaria Fabricius, 1781, by original designation. Polietes domitor (Harris, 1780) Musca domitor Harris, 1780: 148, plate 43 fig. 71. Type-locality: not stated (South-east England). Type-series lost (Pont & Michelsen, 1982: 33). Musca albolineata Fallén, 1823a: 54. Type-locality: Sweden, Skåne, Äsperöd. Lectotype ♂, NHRS (designated by Pont, 1984b: 280). Siberian records: Urals (Zimin & El’berg, 1970: 587); Urals, Zlatoust (Stein, 1916: 20); Yamalo-Nenezkiy AO: Labytnangi, Muzhi (Gagarin & Veselkin, 1987: 215); Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 232); Kurganskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 226); Respublika Altay (Sorokina, 2006b: 139); Yakutskaya Oblast’ (Hennig, 1963c: 911); North Respublika Sakha [Yakutiya]: Verchoyansk, Bagatay (Sychevskaya, 1972: 150); West and East Siberia (Pont, 1986a: 86). General distribution: Palaearctic Region, from Europe east to Japan. Polietes hirticrus Meade, 1887 Polietes hirticrus Meade, 1887: 179. Type-locality: United Kingdom, England, North Yorkshire, Bolton Abbey. Holotype ♂, BMNH (Pont, 1984a: 12). Siberian records: North Respublika Sakha [Yakutiya]: Verchoyansk, Bagatay (Sychevskaya, 1972: 150, 152); West and East Siberia (Pont, 1986a: 86). General distribution: Holarctic Region; in the Palaearctic, from the United Kingdom, Russia (West and East Siberia), Mongolia and China. Polietes lardarius (Fabricius, 1781) Musca lardaria Fabricius, 1781: 436. Type-locality: Germany. Holotype / syntypes,?sex, destroyed, formerly in ZMUC, Fabricius collection (Michelsen, 1979: 185). Siberian records: Urals (Hennig, 1963d: 913); Novosibirskaya Oblast’ (Sorokina, 2006a: 226); near Biysk and Altay Mts (Sychevskaya, 1978: 83); Respublika Altay (Sorokina, 2006b: 139); valley of River Yenisey, taiga: Krasnoyarsk, Yeniseysk (Sychevskaya, 1974: 130); West and East Siberia (Pont, 1986a: 86). General distribution: Palaearctic Region, from Europe east to China; also St Helena Island (Atlantic Ocean). Polietes nigrolimbatus (Bonsdorff, 1866) Aricia nigrolimbata Bonsdorff, 1866: 172. Type-locality: Finland, Kuopio, Tuovilanlahti. Syntypes ♂ ♀, MZH (Stein, 1916: 20). Siberian records: South Urals (Hennig, 1963d: 914; Zimin & El’berg, 1970: 587; Pont, 1986a: 86); Sverdlovskaya Oblast’: Serov, Krasnoufimsk, Talizy, Verkhovino (Zagrebin, 1987a: 232); near Biysk and Altay Mts (Sychevskaya, 1978: 84); Respublika Altay (Sorokina, 2006b: 139); valley of River Yenisey, taiga: Krasnoyarsk, Yeniseysk (Sychevskaya, 1974: 130); South Respublika Sakha [Yakutiya]: Tommot (Sychevskaya, 1972: 150); West and East Siberia (Pont, 1986a: 86). General distribution: Palaearctic Region, from north Europe east to Japan. : Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on pages 30-31, DOI: 10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926 : {"references": ["Rondani, C. (1866) Anthomyinae Italicae collectae distinctae et in ordinem dispositae [a prof. Camillo Rondani]. Atti della Societa Italiana di Scienza Naturali, 9, 68 - 217.", "Fabricius, J. C. (1781) Species insectorvm exhibentes eorvm differentias specificas, synonyma, avctorvm, loca natalia, metamorphosin adiectis observationibvs, descriptionibvs. Volume 2. C. E. Bohnii, Hambvrgi et Kilonii [= Hamburg & Kiel], 517 pp.", "Harris, M. (1780) An exposition of English insects, with curious observations and remarks, wherein each insect is particularly described; its parts and properties considered; the different sexes distinguished, and the natural history faithfully related. The whole illustrated with copper plates, drawn, engraved, and coloured, by the author. Decad 5. \" Printed for the author \", London, pp. 139 - 166, plates 41 - 50.", "Pont, A. C. & Michelsen, V. (1982) The Muscoidea described by Moses Harris (Diptera: Fanniidae, Scathophagidae, Anthomyiidae, Muscidae). Steenstrupia, 8, 25 - 46.", "Fallen, C. F. (1823 a) Monographia Muscidum Sveciae. Part. V. Berlingianis, Lundae [= Lund], pp. 49 - 56.", "Pont, A. C. (1984 b) A revision of the Fanniidae and Muscidae (Diptera) described by Fallen. Entomologica Scandinavica, 15, 277 - 297.", "Zimin, L. S. & El'berg, K. Ya. (1970) Family Muscidae - true flies. In: Stackelberg, A. A. & Narchuk, E. P. (Eds), Keys to the insects of the European part of the USSR in five volumes (general editor G. Ya. Bey-Bienko). V (2). Diptera, Siphonaptera. Nauka, Leningrad [= St Petersburg], pp. 511 - 595. [In Russian.]", "Stein, P. (1916) Die Anthomyiden Europas. Tabellen zur Bestimmung der Gattungen und aller mir bekannten Arten, nebst mehr oder weniger ausfuhrlichen Beschreibungen. Archiv fur Naturgeschichte, 81 A 10 [1915], 224 pp.", "Gagarin, S. N. & Veselkin, G. A. (1987) Features of the fauna and ecology of zoophilous flies (Diptera) on farms of the large horned livestock in Yamalo-Nenetsk AO. In: Cherepanov, A. I. (Ed.), Ecology and geography of arthropods in Siberia. Nauka (Siberian Division), Novosibirsk, 214 - 215. [In Russian.]", "Zagrebin, A. I. (1987 a) On the fauna of pasture flies of the family Muscidae (Diptera) in the Urals. In: Cherepanov, A. I. (Ed.), Ecology and geography of arthropods in Siberia. Nauka (Siberian Division), Novosibirsk, pp. 231 - 233. [In Russian.]", "Sorokina, V. S. (2006 a) Distribution and ecology of house-flies (Diptera, Muscidae) in West Siberia. Euroasian Entomological Journal, 5, 221 - 233. [In Russian, with English abstract.]", "Sorokina, V. S. (2006 b) Contributions to the knowledge of the house-flies (Diptera, Muscidae) of the mountain Altay. In: Materials of the meeting of Siberian and Far East entomologists \" The entomological research in Northern Asia \". Institute of Systematics and Ecology of Animals of Russian Academy of Sciences, Siberian Branch, Novosibirsk, pp. 138 - 140. [In Russian.]", "Hennig, W. (1963 c) Muscidae. [Part, Lieferung 241.] In: Lindner, E. (Ed.), Die Fliegen der palaearktischen Region, 63 b, 865 - 912. Schweizerbart, Stuttgart.", "Sychevskaya, V. I. (1972) On the synanthropic flies of Yakutiya. In: Ammosov, Yu. N. (Ed.), Fauna and ecology of the insects of Yakutiya. Akademiya Nauk SSSR, Yakutsk, pp. 144 - 157. [In Russian.]", "Pont, A. C. (1986 a) Family Muscidae. In: Soos, A. & Papp, L. (Eds), Catalogue of Palaearctic Diptera. Volume 11. Scathophagidae - Hypodermatidae. Akademiai Kiado, Budapest, pp. 57 - 215.", "Meade, R. H. (1887) Supplement to Annotated list of British Anthomyiidae. [Part.] Entomologist's Monthly Magazine, 23, 179 - 181.", "Pont, A. C. (1984 a) The Fanniidae, Anthomyiidae and Muscidae (Diptera) described by R. H. Meade. Entomologist's Monthly Magazine, 120, 7 - 20.", "Michelsen, V. (1979) Notes on the identity and type-material of the Anthomyiidae, Fanniidae, and Muscidae (Diptera) described by J. C. Fabricius. Steenstrupia, 5, 181 - 196.", "Hennig, W. 1963 d. Muscidae. [Part, Lieferung 242.] In: Lindner, E. (Ed.), Die Fliegen der palaearktischen Region, 63 b, 913 - 960. Schweizerbart, Stuttgart.", "Sychevskaya, V. I. (1978) Synanthropic flies (Diptera) of Altay. Entomologicheskoe Obozrenie, 57, 81 - 85. [In Russian.] [English translation in Entomological Review, Washington, 57, 52 - 55.]", "Sychevskaya, V. I. (1974) Synantropic flies from the valley of Enisey River. In: Kolomyiets, N. G. (Ed.), The Fauna and ecology of insects from Siberia. Akademiya Nauk SSSR, Novosibirsk, pp. 128 - 131. [In Russian.]", "Bonsdorff, E. J. (1866) Finlands tvavingade insekter (Diptera), fortecknade och i korthet beskrifne. Andra delen. Bidrag till Kannedom om Finlands Natur och Folk, 7, i - vi, 1 - 306."]}